A vuelo de pájaro: Las ciudades como refugio para las aves (REVISTA NODO, 2009)
The article presents a reflection on bird global distribution, countries with more threatened species and the main causes for this threat, all of them closely related to life in the cities.Using Bogotá as a place of study, the article analyzes the importance of urban birds in the city, their significance as indicators of environment conditions, their overall distribution, some of the urban trees that feed them, and the places where is possible to go watch them. As a conclusion, the paper suggests some recommendations for birds making a comeback in human settlements and, along with them, the quality of the whole environment in urban areas.
Keywords: Birds and cities; urban birds; environment indicator species